Outside theater alliances that shape Mexico - Day, Stuart Alexander (The University of Arizona Press, 2017)
"Outside Theater looks at how written words and performances have been used to promote civic engagement and provoke activism in Mexico"--Provided by publisher
Keywords: Geschichte 1905-2015; Gesellschaft; Theater; Mexiko; Theater and society / Mexico; Theater and society; Mexico